Journey to the Center of the Customer’s Mind - Chaudhuri, Ranjan (Indian Journal of Marketing, 2007)
One of the great buzzwords in recent years has been "customer engagement," generally taken to mean how emotionally involved customers are with a product or brand. And, whatever one calls it, having customers who not only are satisfied with your product but are willing to promote it, defend it, and do battle with others on behalf of it is a great state of being. The article focuses on the emerging concept of neuromarketing and has looked at the science behind neuromarketing in particular. This literature survey is an attempt to widen the scope of neuromarketing beyond commercial brand and consumer behaviour applications, to include a wider conceptualization of marketing science. Neuromarketing offers the prospect of gaining a better understanding of how the brain responds in a wide variety of everyday situations. In addition to proving of great commercial value such research offers the possibility of increasing our knowledge of brain function as it extends powerful medical technologies into a new and challenging area of research. Drawing from general neuroscience and neuroeconomics, neuromarketing as a field of study is defined, and some future research directions are suggested.